Supported Pt Nanoparticles on Mesoporous Titania for Selective Hydrogenation of Phenylacetylene - Hu, Mingzhen; Jin, Lei; Dang, Yanliu; Suib, Steven L.; He, Jie; Liu, Ben (Frontiers in Chemistry, 2020)
Semi-hydrogenation of alkynes to alkenes is one of the most important industrial reactions. However, it remains technically challenging to obtain high alkene selectivity especially at a high alkyne conversion because of kinetically favorable over hydrogenation. In this contribution, we show that supported ultrasmall Pt nanoparticles (2.5 nm) on mesoporous TiO2 (Pt@mTiO2) remarkably improve catalytic performance toward semi-hydrogenation of phenylacetylene. Pt@mTiO2 is prepared by co-assembly of Pt and Ti precursors with silica colloidal templates via an evaporation-induced self-assembly process, followed by further calcination for thermal decomposition of Pt precursors and crystallization of mTiO2 simultaneously. As-resultant Pt@mTiO2 discloses a high hydrogenation activity of phenylacetylene, which is 2.5 times higher than that of commercial Pt/C. More interestingly, styrene selectivity over Pt@mTiO2 remains 100% in a wide phenylacetylene conversion window (20–75%). The styrene selectivity is >80% even at 100% phenylacetylene conversion while that of the commercial Pt/C is 0%. The remarkable styrene selectivity of the Pt@mTiO2 is derived from the weakened styrene adsorption strength on the atop Pt sites as observed by diffuse reflectance infrared Fourier transform spectroscopy with CO as a probe molecule (CO-DRIFTS). Our strategy provides a new avenue for promoting alkyne to alkene transformation in the kinetically unfavorable region through novel catalyst preparation.